PENGELOLAAN BUMDES “CIJEUNGJING BERDIKARI” SEBAGAI PENGGERAK PEREKONOMIAN DESA - Pipih Sopiah; Sirodjul Munir; Neti Sunarti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the management of the Village-Owned Enterprise (BUMDes) 'Cijeungjing Berdikari' as a driver of the economy of Cijeungjing Village, Cijeungjing District, Ciamis Regency. Using a descriptive qualitative approach, this study focuses on the implementation of management functions according to George R. Terry which include planning, organizing, implementing, and monitoring. The results of the study indicate that BUMDes